PENGARUH KADAR GULA TERHADAP KUALITAS SELAI TERONG BELANDA - Kurnia, Tessa; Faridah, Anni; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research based on using oftamarillo fruit in food processing is less, in fact the tamarillo includes a great nutritional degree for healty.The purpose of this research is analysing the effects of using sugar degree on the quality of tamarillo jam, consist of color, smell, texture, and teste. This type of this research is purely experimental with complete randomized design method. The research variables include independent variables withsugar degree as much 40%, 50% and 60% of the total material used. The dependent variable are quality of tamarillo jam. Primary data is sourced from 30 semi-trained by submitting the organoleptic test format. Analysis data with ANAVA, if there is real difference continued with Duncan test. The result of the analysis is there real difference to the use of sugar degree in the quality of maroon color, easy to smear of texture, and sweet acidity of typical tamarillo. On the typical tamarillo smell of quality, typical cinnamon smell and smooth texture have no significant difference. The best results fortamarillo jam is jam with 60% sugar degree.Keywords : Sugar Level, Tamarillo Jam, Quality